Tolerability, safety and intermediary pharmacological effects of cilostazol and isosorbide mononitrate, alone and combined, in patients with lacunar ischaemic stroke: The LACunar Intervention-1 (LACI-1) trial, a randomised clinical trial. (May 2019) - Blair, Gordon W.; Appleton, Jason P.; Flaherty, Katie; Doubal, Fergus; Sprigg, Nikola; Dooley, Richard; Richardson, Carla; Hamilton, Iona; Law, Zhe Kang; Shi, Yulu; Stringer, Michael S.; Thrippleton, Michael J.; et al.
Abstract: Background: Lacunar stroke, a frequent clinical manifestation of small vessel disease (SVD), differs pathologically from other ischaemic stroke subtypes and has no specific long-term secondary prevention. Licenced drugs, isosorbide mononitrate (ISMN) and cilostazol, have relevant actions to prevent SVD progression. Methods: We recruited independent patients with clinically confirmed lacunar ischaemic stroke without cognitive impairment to a prospective randomised clinical trial, LACunar Intervention-1 (LACI-1). We randomised patients using a central web-based system, 1:1:1:1 with minimisation, to masked ISMN 25 mg bd, cilostazol 100 mg bd, both ISMN and cilostazol started immediately, or both with start delayed. We escalated doses to target over two weeks, sustained for eight weeks. Primary outcome was the proportion achieving target dose. Secondary outcomes included symptoms, safety (haemorrhage, recurrent vascular events), cognition, haematology, vascular function, and neuroimaging. LACI-1 was powered (80%, alpha 0.05) to detect 35% (90% versus 55%) difference between the proportion reaching target dose on one versus both drugs at 55 patients. Registration ISRCTN12580546. Findings: LACI-1 enrolled 57 participants between March 2016 and August 2017: 18 (32%) females, mean age 66 (SD 11, range 40–85) years, onset-randomisation 203 (range 6–920) days. Most achieved full (64%) or over half (87%) dose, with no difference between cilostazol vs ISMN, single vs dual drugs. Headache and palpitations increased initially then declined similarly with dual versus single drugs. There was no between-group difference in BP, pulse-wave velocity, haemoglobin or platelet function, but pulse rate was higher (mean difference, MD, 6.4, 95%CI 1.2–11.7, p = 0.02), platelet count higher (MD 35.7, 95%CI 2.8, 68.7, p = 0.03) and white matter hyperintensities reduced more (Chi-square p = 0.007) with cilostazol versus no cilostazol. Interpretation: Cilostazol and ISMN are well tolerated when the dose is escalated, without safety concerns, in patients with lacunar stroke. Larger trials with longer term follow-up are justified. Funding: Alzheimer's Society (AS-PG-14-033).